Feasibility and safety of non-contrast percutaneous coronary intervention in patients with complicated acute coronary syndrome. (25th November 2020) - Higuchi, S; Kabeya, Y; Nishina, Y; Miura, Y; Yoshino, H
Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) occurs in 10% to 20% of acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI), resulting in a poor short- and long-term prognosis. Reducing the amount of contrast medium can prevent CI-AKI. Objectives: This study aimed to examine the feasibility and safety of non-contrast PCI in patients with ACS. Methods: The study was a prospective and single-center registry. Successful non-contrast PCI was confirmed when contrast medium was not injected from the guiding catheter engagement to wire removal in ad-hoc PCI. Coronary angiography after the PCI procedure was permitted once. CI-AKI was defined as an increase in the serum creatinine of ≥0.5 mg/dL from or ≥1.25 times the baseline within 72 hours after PCI. Worsening renal function (WRF) was defined as an increase in the serum creatinine of ≥0.3 mg/dL from baseline after the PCI. Results: The present study included 106 lesions from 81 patients. Forty-eight lesions were (45%) type C lesions. Successful non-contrast PCI was performed in 95 lesions (90%). CI-AKI was observed in 4 (5%); coronary perforation, 0; no/slow flow, 9 (11%); periprocedural death, 0. The follow-up period was 348 (190–492) days. Successful non-contrast PCI was not associated with the incidence of CI-AKI. However, WRF at 6-month was observed in 18 individuals (22%). Successful non-contrast PCI was inversely associated with WRF (hazard ratio, 0.28; 95% confidence interval, 0.09–0.90) after adjustment for renal function. Conclusions: The present study suggests that non-contrast PCI is feasible and safe in ACS patients with complex lesions. Funding Acknowledgement: Type of funding source: None